Alterations of long noncoding RNAs and mRNAs in extracellular vesicles derived from the murine heart post‐ischemia–reperfusion injury. Issue 24 (28th November 2022) - Ge, Xinyu; Meng, Qingshu; Liu, Xuan; Liu, Jing; Ma, Xiaoxue; Shi, Shanshan; Li, Mimi; Lin, Fang; Liang, Xiaoting; Gong, Xin; Liu, Zhongmin; Han, Wei; et al.
Abstract: Extracellular vesicles (EVs) play important roles in cardiovascular diseases by delivering their RNA cargos. However, the features and possible role of the lncRNAs and mRNAs in cardiac EVs during ischemia–reperfusion (IR) remain unclear. Therefore, we performed RNA sequencing analysis to profile the features of lncRNAs and mRNAs and predicted their potential functions. Here, we demonstrated that the severity of IR injury was significantly correlated with cardiac EV production. RNA sequencing identified 73 significantly differentially expressed (DE) lncRNAs (39 upregulated and 34 downregulated) and 720 DE‐mRNAs (317 upregulated and 403 downregulated). Gene Ontology (GO) and pathway analysis were performed to predict the potential functions of the DE‐lncRNAs and mRNAs. The lncRNA‐miRNA‐mRNA ceRNA network showed the possible functions of DE‐lncRNAs with DE‐mRNAs which are enriched in the pathways of T cell receptor signalling pathway and cell adhesion molecules. Moreover, the expressions of ENSMUST00000146010 and ENSMUST00000180630 were negatively correlated with the severity of IR injury. A significant positive correlation was revealed between TCONS_00010866 expression and the severity of the cardiac injury. These findings revealed the lncRNA and mRNA profiles in the heart derived EVs and provided potential targets and pathways involved in cardiac IR injury.